Impact of Information and System Quality on User Satisfaction with Outpatient EMRs at RSKIA Sadewa, Indonesia - Putri, Dela Astia; Sutrisno, Trismianto Asmo (Journal of Intelligent Computing & Health Informatics, 2024)
The use of electronic medical records (EMR) in outpatient services continues to increase, however, many hospitals still face challenges in ensuring optimal adoption and user satisfaction. Previous research suggests that issues related to information quality and system stability may hinder the effective use of EMRs, but not many studies have specifically analyzed these two factors in the context of regional hospitals. This study aimed to evaluate the effect of information and system quality on EMR user satisfaction in RSKIA Sadewa, Yogyakarta, and identify strategic improvement steps. Primary data were collected from 42 questionnaires distributed to EMR users, and 37 responses were analyzed using multiple linear regression. Results showed that system quality (β = 0.213, p < 0.05) and information quality (β = 0.199, p < 0.05) had a significant influence on user satisfaction, with a joint contribution of 81.1% (R² = 0.811). Although the system provided sufficient features, system reliability constraints and incomplete information negatively affected user experience. System menu optimization and regular training are proposed as strategic measures to improve operational effectiveness. The findings provide important insights for hospital managers and policymakers regarding the importance of strengthening IT infrastructure and data validation to support more effective EMR implementation. Further research is recommended to involve various hospitals in different contexts to expand external validity and provide more comprehensive recommendations for the healthcare sector.